Implementasi Pembangunan Ekonomi di Indonesia Bersifat Unsustainable? - Yanuarti, Wella Amalia; Rachmawati, Lucky (Independent: Journal of Economics, 2022)
Sustainable development is a measure of development that takes into account economic, social and environmental aspects. The achievement of measuring development with GDP is unable to measure people’s welfare and does not take into account aspects of environmental damage. Development in Indonesia is short-term and suffers from a trap of progress that damages the environment. This study aims to measure the achievements of sustainable development in Indonesia using the sustainable development index. The results of the study using the IPB 2 scenario are better than scenario 1. Based on scenario 2, it is unsustainable development with a sloping u-inverted curve according to the environmental kuznet curve hypothesis. Research shows that achieving sustainable development is shown by balancing the rate of growth with the rate of population. In achieving sustainable development, measures of sustainable development are needed for the scope of areas that are environmentally sound, as well as the implementation of carbon tax policies.